BIOLOGICALLY SUBSTANTIATED, SAFE, AND CORRECTIVE REMEDIES FOR SARS-COV-2 REGIMEN - Amirova, M.F.; Huseynova, E.E.; Melikova, N.V.; Mammаdova F.I.; Azizova, U.H.; Guliyeva, S.R. (World of Medicine and Biology, 2025)
The paper seeks to find a novel effective treatment way for Severe Acute Respiratory Syndrome COVID-2 (SARS-CoV-2) without harm to the organism in general. Taking into account the information on the mechanism of of SARS-CoV-2 development, during treatment, it is advisable to pay attention to inhibition of viral replication; reduction hypoxia; elimination drug poisoning and toxic, allergic consequences; add antioxidant therapy to prevent formation of reactive oxygen species (ROS) at recovery phase and hook up anti-inflammatory therapy. This goal could be achieved by enhancing antiviral defense, administering antioxidants, and activating antioxidant enzymes according to their action mechanisms and therapeutic implications. For example, using superoxide dismutase mimics metalloporphyrins, metallocorroles, Mn biliverdins, Mn cyclic polyamines, Mn salens, metal oxides/salts and inducers of antioxidant protection. It is also possible to increase the antioxidant enzymes genes expression or the activity of the enzyme itself. Patients taking antibiotics for SARS-CoV-2 were more susceptible to exacerbations due to opportunistic infections, so alternatives to antibiotics with high efficacy and well-absorbed antioxidant properties are more appropriate. In this regard, vitamin C, N-acetylcysteine, and glycine, as well as melatonin, quercetin, astaxanthin, glutathione, fat-soluble vitamins, polyphenols, unsaturated fatty acids, and a number of other substances with high anti-inflammatory effects exhibit positive effect.